Relationship Between Waist Circumference, Smoking, and Physical Activity with Hypertension at Lenek Community Health Center - Fikri, Lalu Muhammad Farros; Utama, Lalu Buly Fatrahady; Rinayu, Nisia Putri; Ariyanto, Suwondo (Jurnal Biologi Tropis, 2025)
Non-Communicable Diseases (NCDs), including hypertension, are a major problem and cause of premature death in developing countries. Data on hypertension in NTB is 282,970 with the most sufferers in East Lombok Regency. Non-modifiable hypertension risk factors include age, gender, and heredity, as well as modifiable risks include smoking, alcohol use, obesity, nutrition, and physical activity. The purpose of this study at the Lenek Health Center is to evaluate the link between waist circumference, smoking, and physical activity with hypertension. This study employs a cross-sectional approach and is observational quantitative analytical in nature. Purposive sampling is done using the Slovin formula. This study's sample size was 106 samples. The data was examined using the chi-square test. The findings revealed 106 respondents, the majority of whom had hypertension (74 people, 69.8%), while 32 people (30.2%) did not have hypertension. There is a substantial correlation between waist circumference and hypertension (p = 0.001). Smoking is significantly associated with hypertension (p=0.001). There is a strong link between physical activity and hypertension (p=0.001). The conclusion is that waist circumference, smoking, and physical activity all influence the prevalence of hypertension at the Lenek Health Center.